2014
DOI: 10.1007/s11881-014-0092-5
|View full text |Cite
|
Sign up to set email alerts
|

Orthographic learning in dyslexic Spanish children

Abstract: Reading fluency is one of the basic processes of learning to read. Children begin to develop fluency when they are able to form orthographic representations of words, which provide direct, smooth, and fast reading. Dyslexic children of transparent orthographic systems are mainly characterized by poor reading fluency (Cuetos & Suárez-Coalla 2009; Spinelli, De Luca, Di Filippo, Mancini, Martelli, & Zoccolotti, 2005; Wimmer, 1993). Therefore, the main problem for these children could be the difficulty in developi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 40 publications
2
33
0
5
Order By: Relevance
“…Even though reading speed increased over time, the authors concluded that poor and beginning readers still relied on the indirect route of reading. In a similar study, Suárez-Coalla, Ramos, Álvarez-Cañizo, and Cuetos (2014) showed that the length effect decreased in typically reading Spanish children (aged 7-12) but lasted in dyslexic children. The study of Martens and De Jong (2008) was on beginning readers of Dutch, an orthographically transparent language.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Even though reading speed increased over time, the authors concluded that poor and beginning readers still relied on the indirect route of reading. In a similar study, Suárez-Coalla, Ramos, Álvarez-Cañizo, and Cuetos (2014) showed that the length effect decreased in typically reading Spanish children (aged 7-12) but lasted in dyslexic children. The study of Martens and De Jong (2008) was on beginning readers of Dutch, an orthographically transparent language.…”
mentioning
confidence: 80%
“…They concluded that repeated reading of single words did lead to automatization in typically reading children, but not in poor readers. With regard to the DRC model, this implies that poor readers of Dutch (and other orthographically transparent languages (e.g., Spanish; Suárez-Coalla et al, 2014)) are thought to keep relying on the indirect route of reading (i.e., phonological recoding), whereas typically developing readers have automatized reading and move towards direct reading, at least after 16 repetitions.…”
mentioning
confidence: 99%
“…Finally, a follow-up session was conducted to verify the resistance to decay of orthographic representations. Orthographic learning was measured by the decrease of length effect (RTs) after the repeated reading (six times) of the new words, a paradigm with significant potential as an instrument for investigating visual word learning (Kwok & Ellis, 2014; Suárez-Coalla, Suárez-Coalla, Avdyli, & Cuetos, 2014;Suárez-Coalla, Ramos, Álvarez-Cañizo, & Cuetos, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that Spanish children with dyslexia use a sub-lexical strategy to read; however, problems in storing orthographic representations of words after repeated readings were also described in children with dyslexia (Suárez-Coalla et al, 2014). Therefore, we were interested in identifying the key features of dyslexia among Spanish adults.…”
Section: Introductionmentioning
confidence: 99%